HUBUNGAN PARITAS DAN DUKUNGAN SUAMI TERHADAP PEMBERIAN ASI EKSKLUSIF - Fajria Maulida, Luluk; Ernita, Ernita; Titisari, Ira; Juniarti, Rizky Auliah; Hadijah, Hadijah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on data findings from the Jambi City Health Office, the Paal X Health Center experienced a significant downward trend in data and was the lowest health center in exclusive breastfeeding. Initial surveys conducted at the Paal X Health Center showed that there were several mothers who gave breast milk but were assisted by formula milk before the age of 6 months. The purpose of the study was to determine the relationship of parity and husband support to exclusive breastfeeding. This type of research uses quantitative with a cross sectional approach. The research was conducted in June 2022 using incidental sampling. The sample amounted to 90 people. The results showed that there was a relationship between husband support and exclusive breastfeeding (p value = 0.000) and there was no relationship between parity and exclusive breastfeeding (p value = 0.098). It is recommended that the Paal X Health Center provide a more intensive socialization or counseling program for nursing mothers or pregnant women, as well as their families. So that not only in the health center, counseling outside the health center can also be done such as posyandu. Keywords: Exclusive breastfeeding, family support, parity